2020
DOI: 10.1093/rheumatology/kez590
|View full text |Cite
|
Sign up to set email alerts
|

MRP8/14 and neutrophil elastase for predicting treatment response and occurrence of flare in patients with juvenile idiopathic arthritis

Abstract: Objective To study two neutrophil activation markers, myeloid-related protein (MRP) 8/14 and neutrophil elastase (NE), for their ability to predict treatment response and flare in patients with JIA. Methods Using samples from two cohorts (I and II), we determined MRP8/14 and NE levels of 32 (I) and 81 (II) patients with new-onset, DMARD-naïve arthritis and compared patients who responded to treatment (defined as fulfilling ≥ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 18 publications
0
23
2
Order By: Relevance
“…When tested alone or incorporated into multivariate models, S100A8/S100A9 proteins have shown higher predictive power when determining treatment response than clinical variables such as ESR or CRP (42, 44). However recently, a Dutch study involving 123 patients with early non-systemic JIA, mostly RF negative polyarticular subtype, reported no difference in baseline MRP8/14 levels between responders (patients who achieved at least a ACRPedi50 response) and non-responders, though patients in this study received different DMARDs ( Barendregt et al, 2020 ). Another observational study which measured the baseline levels of MRP8/14 in 152 non-systemic JIA patients before starting anti-TNF treatment, demonstrated that patients who reached inactive disease at 12 months had higher levels compared to patients who did not ( Alberdi-Saugstrup et al, 2017 ).…”
Section: Potential Role Of Measuring Proinflammatory Proteins In Serumentioning
confidence: 56%
See 2 more Smart Citations
“…When tested alone or incorporated into multivariate models, S100A8/S100A9 proteins have shown higher predictive power when determining treatment response than clinical variables such as ESR or CRP (42, 44). However recently, a Dutch study involving 123 patients with early non-systemic JIA, mostly RF negative polyarticular subtype, reported no difference in baseline MRP8/14 levels between responders (patients who achieved at least a ACRPedi50 response) and non-responders, though patients in this study received different DMARDs ( Barendregt et al, 2020 ). Another observational study which measured the baseline levels of MRP8/14 in 152 non-systemic JIA patients before starting anti-TNF treatment, demonstrated that patients who reached inactive disease at 12 months had higher levels compared to patients who did not ( Alberdi-Saugstrup et al, 2017 ).…”
Section: Potential Role Of Measuring Proinflammatory Proteins In Serumentioning
confidence: 56%
“…In the first study, MRP8/14 or S100A12 were not significantly different between 39 patients with extended oligoarticular of polyarticular disease who flared within 8 months of anti-TNF treatment withdrawal and 67 patients who remained clinically inactive off biologic treatment ( Hinze et al, 2019 ). In the other study, MRP8/14 was tested in two cohorts of non-systemic JIA patients, including 88 patients (27 on anti-TNF treatment) with inactive disease after 12 months of treatment ( Barendregt et al, 2020 ). Levels of MRP8/14 did not predict the development of joint inflammation defined as an active joint count ≥1 at 6 or 12 months post treatment cessation on either cohort.…”
Section: Various Predictor Biomarkers For Successful Withdrawal Of Bimentioning
confidence: 99%
See 1 more Smart Citation
“…Our study underlines thus a group of patients at risk of relapse who could bene t from a more frequent monitoring during a longer period of time, even if in a seemingly reassuring remission state. Another recent study could not nd a relationship between sCal and the prediction of response to treatment and are; this study excluded systemic forms (which could be more in ammatory and aggressive, thus maybe more related to variations of sCal) and comprised two very different cohorts (30). Overall, it underlines the fact that JIA is a very heterogeneous disease that translates into few comparable studies.…”
Section: Discussionmentioning
confidence: 95%
“…A prospective non-randomized clinical trial studying strati ed therapeutic approaches based on biomarkers in patients with a polyarticular course has just completed recruitment and results are awaited for December 2020 (ISRCTN 69963079). In light of recent results (29,30), it could also be interesting to study sCal in oligoarticular and systemic forms to evaluate its e cacy as a prognosis marker in other speci c subgroups of patients (results from Hinze et al tended to show that dosage of sCal under stable treatment could be discriminating in extended oligoarthritis and seropositive polyarthritis, but not in seronegative polyarthritis). Evaluating levels of sCal in patients tapering their treatment without discontinuing it totally could also be of interest.…”
Section: Discussionmentioning
confidence: 99%